2011
DOI: 10.5223/kjpgn.2011.14.suppl1.s55
|View full text |Cite
|
Sign up to set email alerts
|

Underweight in Adolescents

Abstract: There are few studies of underweight in adolescents in Korea and other developed countries. According to the recent surveillance in Korea, prevalence of underweight in adolescents is lower than those in developing countries, and higher than those in developed countries in Northern Europe. This article reviews the problems, diagnosis, and nutritional support of underweight in adolescents. 저체중 현황에 대한 해외 보고는 개발도상국 위주로

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Obesity can have adverse effects on adolescents. In addition, being underweight adversely affects brain growth, recovery, and secondary sexual characteristics in adolescents (Shim, 2011 ). It is, thus, important to maintain a healthy weight in adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity can have adverse effects on adolescents. In addition, being underweight adversely affects brain growth, recovery, and secondary sexual characteristics in adolescents (Shim, 2011 ). It is, thus, important to maintain a healthy weight in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Being underweight during adolescence has several negative consequences, such as delaying secondary sexual characteristics and hindering learning ability and school life. Being underweight during this life stage can, thus, negatively impact not only adulthood but also the next generation (Shim, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous study, the probability of trying to lose weight through vomiting after eating was 1.62 times higher than regular exercise for weight loss in adolescents, confirming an inappropriate attempt to lose weight [ 18 ]. Another study found that 13.4% of adolescents fasted for weight loss, and they were performing weight loss activities, such as taking diet pills or laxatives and vomiting [ 19 ]. Excessive dietary restrictions for weight control in adolescence may cause musculoskeletal growth and sexual maturation delays or may negatively affect school life due to reduced learning ability and concentration [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that 13.4% of adolescents fasted for weight loss, and they were performing weight loss activities, such as taking diet pills or laxatives and vomiting [ 19 ]. Excessive dietary restrictions for weight control in adolescence may cause musculoskeletal growth and sexual maturation delays or may negatively affect school life due to reduced learning ability and concentration [ 19 ]. In the results of this study, the association between inappropriate weight loss and body image distortion can be considered, so it is necessary to examine their association in depth in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that excessive weight loss in adolescents can lead to a number of potentially detrimental health consequences, including malnutrition and subsequent growth delays (Neumark-Sztainer et al , 2002; Ojala et al , 2007). Special attention should be paid to female adolescents because excessive weight-loss attempts in this life stage, when they are to prepare for childbearing in adulthood, can cause subsequent maternal and child health problems such as amenorrhoea, infertility and low birth-weight infants (Shim, 2011; Van der Spuy et al , 1988). Specifically, calcium and vitamin A, of which intake levels were inadequate in our study, are closely related to adolescent growth.…”
Section: Discussionmentioning
confidence: 99%